Toward Safer and More Productive Migration for South Asia - Ahmed, Amer (Washington, DC: World Bank, 2022)
International migration for temporary employment is key to South Asia’s development path, in terms of both jobs and remittance flows. Overseas markets are a critical source of employment for South Asian economies that may not be able to absorb workers sufficiently or quickly enough into the domestic labor market. Migrant workers typically experience wage gains of at least three times their earnings back home, in addition to acquiring new skills and accumulating savings that can be used to start up entrepreneurial activities upon returning home. Remittances sent by migrants while abroad also boost household consumption and support macroeconomic stability in countries of origin.